Polymyalgia rheumatica: causes, symptoms, diagnosis, treatment, and outlook - Dasgupta, Bhaskar (Henry Stewart Talks, 2023)
Pathophysiology and approach to PMR, 2015 EULAR ACR and 2009 BSR recommendations, Over-arching principles, Early specialist referral, Disability and QOL in PMR, Assessment of PMR, Glucocorticoids, Steroids or bust?, Methotrexate/leflunomide/biologics, Role of exercise in PMR